Social Security Guide : The White Paper and the Beveridge Report Compared - Great Britain. Office of the Minister of Reconstruction. Social insurance ; Great Britain. Inter-departmental Committee on Social Insurance and Allied Services. Social insurance and allied services ; Beveridge, William Henry Beveridge, Baron, 1879-1963; Clarke, Joan Simeon (London : The Social Security League)
1944-10-01 1944 1940s 20 pages Industrial Injury Insurance shall be at a flat rate irrespective of earning. The Beveridge proposals would have the effect of paying 90 per cent. of all injured workmen at a flat rate. The Government will pay a flat rate to them all. If this be enacted, Great Britain will be the pioneer country in this respect. Lastly, the Government agree to abolish lump sum payments. The Government differ from Sir William on two points. First, there will be no industrial levy. The scheme will be financed entirely by flat rate contributions from employees, employers and the State. There will thus be no financial incentive to employers to reduce the accident rate in their industries. The Government wish to promote safety by other forms of industrial legislation, inspection and co-operation. Secondly, the Government does not propose to assess pensions for partial disablement on loss of earning power. The disabled person will be examined by a medical board which will compare his condition after injury to that of a normal healthy person of the same age and sex. The pension rate will be fixed as the basis of this medical report and will not be affected by previous earnings. The Government scheme, though generally under the Minister of Social Insurance, will be run outside the normal scheme. All claims will be handled by specialised Industrial Pensions Officers. There will be right of appeal to local tribunals of employers and workmen, and, finally, to an Industrial Injury Insurance Commission. The problem of damages which might be awarded against the employer as the result of Common Law claims will be considered by a Committee, recommended by Sir William Beveridge and now set up by the Government with Sir Walter Monckton as its Chairman.* 11. THE COST— The White Paper Plan would cost the nation £47 less in 1945 than the Beveridge Plan. The Government Actuary explains the saving like this:— Industrial injury omitted from Social Security budget £17m. saved Health service will not reach full cost by 1945 ............ £22m. „ Reduction in family allowances £40m. „ Reduced cost of unemployment and sickness benefit and assistance £10m. „ Miscellaneous unspecified saving £3m. „ £92m. „ Add increased cost of retirement and widows' pensions £45m. „ Net saving £47m. „ This shows clearly how the Government have shifted the emphasis from the young to the elderly. Out of £45m. increase on retirement and widows' pensions, £40 comes from the cut on children's allowances. *NOTE.— These few paragraphs are intended only to indicate the main points of discussion. Readers are advised to read the Workmen's Compensation White Paper, Cmd. 6551, September, 1944, H.M.S.O. 3d. It gives a brilliantly lucid account of what had seemed to be a complicated subject. 16 15X/2/453/3